Uncertainty and risk of misleading conclusions: an umbrella review of the quality of the evidence for ankle arthroscopy - Ville Ponkilainen; Valtteri Panula; Juho Laaksonen; Anniina Laurema; Mikko Miettinen; Ville M Mattila; Teemu Karjalainen (Acta Orthopaedica, 2025)
Background and purpose: Ankle arthroscopy is being increasingly utilized, but its potential benefits and harms remain unclear. This umbrella review aimed to assess the quality of systematic reviews and meta-analyses comparing ankle arthroscopy with equivalent open procedures or nonoperative options. Methods: A comprehensive search of MEDLINE, Embase, and CENTRAL was conducted on March 22, 2025. 2 reviewers independently screened abstracts and full texts, with conflicts resolved by a third reviewer. Systematic reviews assessing ankle arthroscopy versus any surgery or nonoperative treatment were included. The methodological quality of the reviews was evaluated using AMSTAR 2 criteria, along with an evaluation of whether the GRADE tool was appropriately applied. Results: The literature search identified 430 studies, of which 29 systematic reviews were included after the screening process. These reviews covered various conditions, including lateral ankle instability, osteoarthritis, fractures, and osteochondral defects. None of the systematic reviews included RCTs comparing arthroscopic procedures with nonoperative treatment. A methodological assessment using AMSTAR 2 criteria identified multiple critical flaws across all reviews, leading to an overall confidence rating of “critically low” for each. 1 study adequately applied the GRADE approach to assess the certainty of the evidence. Conclusion: The efficacy of ankle arthroscopic procedures remains based solely on observational evidence. Given the critically low methodological quality of existing reviews, conclusions suggesting benefits of ankle arthroscopy, particularly over open procedures, are unreliable and insufficient to inform clinical recommendations. RCTs comparing ankle arthroscopy with nonoperative treatments or sham surgery are urgently needed.